Elemental concentrations in skin and internal tissues of Commerson’s dolphins (Cephalorhynchus commersonii) from subantarctic waters - Cáceres Saez, Iris; Ribeiro Guevara, Sergio; Prosser Goodall, Rae Natalie; Dellabianca, Natalia Andrea; Cappozzo, Humberto Luis (Polar Biology)
The skin of cetaceans is the most accessibletissue, and its sampling has been proposed as a noninvasivemethod to evaluate trace element concentrations in free-rangingpopulations. In the present work, concentrations ofessential (Cl, Na, K, Mg, Fe, Zn, Mn and Co), nonessential(As and Ag), and of unknown essentiality (Br, Rb and Cs)elements were determined in the skin from nine by-caughtCommerson´s dolphins (Cephalorhynchus commersonii)from Tierra del Fuego, Argentina. Skin correlations withinternal tissues (lung, liver, kidney and muscle) wereassessed to evaluate how the skin represents internal elementconcentration for monitoring purposes. Elementalcontents were analyzed by instrumental neutron activationanalysis (INAA). Regarding tissue distribution, skin hadthe highest concentration of Zn being two orders of magnitudehigher than internal tissues, while other elementssuch as Co and Rb had similar concentrations among tissues.High mean concentrations of Cl, Na, Mg, Br and Mnwere observed in the lung and liver. Our results support theuse of skin to evaluate Fe, Br and Rb concentrations ininternal tissues for biomonitoring purposes; however, otherelements did not show significant skin-to-tissue correlations.Overall, toxic element levels were far below concentrationsfound to cause harm in marine vertebrates. Thisstudy provided baseline data on elemental concentrationsin tissues of Commerson´s dolphins in subantarctic watersfrom the South Atlantic Ocean. Fil: Cáceres Saez, Iris. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina. Museo Acatushún de Aves y Mamíferos Marinos Australes; Argentina Fil: Ribeiro Guevara, Sergio. Comisión Nacional de Energía Atómica. Gerencia del Área de Energía Nuclear. Unidad de Actividad de Ingeniería Nuclear. Laboratorio de Análisis por Activación Neutróica; Argentina Fil: Prosser Goodall, Rae Natalie. Consejo Nacional de Investigaciones ...